Identification of novel piRNAs in bladder cancer. Issue 2 (28th January 2015) - Chu, Haiyan; Hui, Gaoyun; Yuan, Lin; Shi, Danni; Wang, Yubang; Du, Mulong; Zhong, Dongyan; Ma, Lan; Tong, Na; Qin, Chao; Yin, Changjun; Zhang, Zhengdong; et al.
Abstract: PIWI-interacting RNAs (piRNAs) are a newly identified class of small non-coding RNAs that can play important roles in germline development and carcinogenesis. In this study, piRNA microarrays were used to investigate global piRNA expression in three bladder cancer tissues and their adjacent normal tissues. Using the 3' untranslated region (UTR) sequence complementarily method, we predicted the target gene of piRNA. Our results showed that the expression levels of 106 piRNAs were up-regulated and 91 were down-regulated in bladder cancer tissues, among which the fold-change of down-regulated piRNA DQ594040 associated with bladder cancer (piRABC) was the highest piRNA. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to confirm piRABC expression in paired bladder cancer tissues and their adjacent normal tissues ( n = 25). Over-expression of piRABC can inhibit bladder cancer cell proliferation, colony formation, and promote cell apoptosis (all P < 0.05). Luciferase reporter gene assays indicated that piRABC could increase the luciferase activity of TNFSF4. Western blotting analyses and ELISA assays also confirmed that the expression of TNFSF4 protein was up-regulated in control subjects compared with bladder cancer subjects. In conclusion, piRABC plays a crucial role in the development of bladder cancer.